2018
DOI: 10.1002/cbic.201800157
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carboxylic Acid Reductases for Biocatalytic Synthesis of Industrial Chemicals

Abstract: Carboxylic acid reductases (CARs) catalyze the reduction of a broad range of carboxylic acids into aldehydes, which can serve as common biosynthetic precursors to many industrial chemicals. This work presents the systematic biochemical characterization of five carboxylic acid reductases from different microorganisms, including two known and three new ones, by using a panel of short-chain dicarboxylic acids and hydroxy acids, which are common cellular metabolites. All enzymes displayed broad substrate specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
2
34
1
Order By: Relevance
“…Overall, Tv CAR showed activity in a rather broad range from pH 6.0‐8.0 without losing activity considerably (Figure A). This observation was consistent with the biophysical characterizations of other CARs . The pH optimum determined for Tv2 CAR and Ds CAR showed the highest relative activity at pH 7.5 in 100 mM bicine‐ NaOH buffer and showed a preference for neutral to basic aqueous environment (Figure B–C).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Overall, Tv CAR showed activity in a rather broad range from pH 6.0‐8.0 without losing activity considerably (Figure A). This observation was consistent with the biophysical characterizations of other CARs . The pH optimum determined for Tv2 CAR and Ds CAR showed the highest relative activity at pH 7.5 in 100 mM bicine‐ NaOH buffer and showed a preference for neutral to basic aqueous environment (Figure B–C).…”
Section: Resultssupporting
confidence: 87%
“…Consequently, it can be concluded that type IV fungal CARs showed no significantly reduced activity up to 35 °C and Tv CAR even remained active up to 50 °C when incubated for 1 h at the specific temperatures. Up to date only the bacterial Mav CAR was described to be more thermostable and active at temperatures higher than 40 °C . Hence, Tv CAR would be a good fungal candidate when increased thermostability is needed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, several biological routes to carboxylic acid reduction are known including direct reduction, catalyzed by a single enzyme or two-enzyme cascades with thioester or phosphoester intermediates (Kramer et al, 2018;Napora-Wijata et al, 2014).…”
Section: Introductionmentioning
confidence: 99%